2012
DOI: 10.1038/ejhg.2012.52
|View full text |Cite
|
Sign up to set email alerts
|

Lactose malabsorption is a risk factor for decreased bone mineral density in pancreatic insufficient cystic fibrosis patients

Abstract: As decreased bone mineral density (BMD) is a common problem in cystic fibrosis (CF) and milk products may have pivotal dietary role affecting BMD, we aimed to assess the potential influence of adult-type hypolactasia (ATH) and lactose malabsorption (LM) on BMD in adolescent and young adult patients. In 95 CF pancreatic-insufficient patients aged 10-25 years (without liver cirrhosis, steatosis and cholestasis, diabetes mellitus, systemic glucocorticoid therapy), lumbar BMD, the nutritional status, pulmonary fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, the study group included only fourteen patients from 5 to 19 years old. The third study reported reduced bone mineral density in patients with CF between 10 and 25 years old with adult-type hypolactasia and lactose malabsorption, which were confirmed as independent predictors of reduced bone mineral density [23].…”
Section: Discussionmentioning
confidence: 95%
“…However, the study group included only fourteen patients from 5 to 19 years old. The third study reported reduced bone mineral density in patients with CF between 10 and 25 years old with adult-type hypolactasia and lactose malabsorption, which were confirmed as independent predictors of reduced bone mineral density [23].…”
Section: Discussionmentioning
confidence: 95%
“…Some studies reported that a reduced value of a quantitative ultrasound (QUS) variable, both velocity- and attenuation-based, was associated with a reduced BMS in children with growth problems or disorders affecting bone health [ 11 , 12 , 13 , 14 ]. One study examined the correlation between ATH and bone mineral density (BMD), but their subjects were also affected by cystic fibrosis [ 15 ], and the authors used dual-emission X-ray absorptiometry (DXA) instead of QUS. Our study also provides an overview of Ca intake from different foods that are a source of Ca and vitamin D.…”
Section: Introductionmentioning
confidence: 99%
“…An association between BMI and BMD has been noted in the literature previously . This would suggest that increased focus on improving nutritional status in patients with CF would cause bone density to improve accordingly.…”
Section: Discussionmentioning
confidence: 74%
“…27 An association between BMI and BMD has been noted in the literature previously. 7,28 This would suggest that increased focus on improving nutritional status in patients with CF would cause bone density to improve accordingly. However, a study comparing two cohorts of CF patients, one cohort studied 15 years ago and one cohort in the present day period found that BMI was not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%